Whole-genome sequencing and comparative genomic analysis of Escherichia coli O91 strains isolated from symptomatic and asymptomatic human carriers. Issue 1 (December 2016) - Kwon, Taesoo; Bak, Young-Seok; Jung, Young-Hee; Yu, Young-Bin; Choi, Jong; Kim, Cheorl-Ho; Kim, Jung-Beom; Kim, Won; Cho, Seung-Hak
Abstract Background The Shiga toxin–producingEscherichia coli (STEC) O91:H21 strains NCCP15736 and NCCP15737 were isolated during a single outbreak in Korea, NCCP15736 from a symptomatic carrier and NCCP15737 from an asymptomatic carrier. To investigate genomic differences between the two strains, we performed whole-genome sequencing of both strains and conducted a comparative genomic analysis. Results Using the Illumina HiSeq 2000 platform and Rapid Annotation using the Subsystem Technology (RAST) server, whole-genome sequences of NCCP15736 and NCCP15737 were obtained and annotated. Phylogenetic analysis of tenE. coli strains showed that NCCP15736 and NCCP15737 are evolutionarily close. The two strains were found to be most close toE. coli O91:NM str. 2009C-3745. The genomic comparison showed that thefimD gene of NCCP15737 is truncated and that the truncation could underlie the defects in infection and pathogenicity of NCCP15737. The two strains showed the same virulence factor profiles, and we identified 25 virulence factors from NCCP15736 and NCCP15737, respectively. We identified ten and nine phage-associated regions in the NCCP15736 and NCCP15737 genomes, respectively; the two strains share five of these. Conclusions NCCP15736 and NCCP15737 differ at the genomic level, even though they share features such as virulence-related genes. NCCP15737 has a deletion infimD, which may underlie its asymptomatic character. We conclude that complete genome sequencing and integration of other types of omics data are needed to fully reveal the mechanism underlying the asymptomatic character of NCCP15737.